PENGARUH TATA KELOLA PERUSAHAAN DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN - Hariati, Isnin; P, Yeney Widya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aimed to examine the influence of corporate governance and environmental performance to firm value. Corporate governance was identified by the proportion of institusional ownership, the proportion of independent commissioner board, and number of audit committee. Firm value was proxied by Tobin’s Q (market- based financial performance), while environmental performance was measured by PROPER issued by the Indonesian State Ministry of Environmental. The study used 81 companies as a sample from a population of 447 manufacturing companies listed on Indonesian Stock Exchange in the period of 2011-2013. The sample was determined by using purposive sampling. The results showed that corporate governance mechanisms proxied by the proportion of independent commissioner board had positive effect on firm value, while the proportion of institusional ownership and number of audit committee had a negative effect on firm value. In other side, these results proved that there was positive effect of environmental performance on firm value Keywords: Corporate governance, environmental performance, firm value.